A monograph on the isopod family Aegidae in the Tropical Eastern Pacific I The genus Aega - Brusca, R.C. (Los Angeles, California Allan Hancock Foundation : Institute for Marine and Coastal Studies, University of Southern California, 1983)
Allan Hancock monographs in marine biology ; no. 12
Keywords: Crustacea--South Pacific Ocean--Classification.; Aegidae--South Pacific Ocean--Classification.